Colfax Communities and a few more - Stanley, F. (Raton, New Mexico Coda Productions, 2006)
Item is a facsimile reproduction and collection of Father Stanley's histories of a number of communities in Colfax County, New Mexico. The histories were originally issued as separates and published between 1962 and 1972.
Capulin Story : Farley Story : Johnson Mesa Story : Miami Story : Maxwell Story : Otero Story : Roy Story : Wagon Mound Story : Watrous Story
106177
Keywords: History -- Capulin, NM; History -- Farley, NM; History -- Johnson Mesa, NM; History -- Miami, NM; History -- Otero, NM; History -- Roy, NM; History -- Wagon Mound, NM; History -- Watrous, NM; History -- Maxwell, NM